2021
DOI: 10.1101/2021.02.12.430954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelial alpha globin is a nitrite reductase

Abstract: Small artery vasodilation in response to hypoxia is essential for matching oxygen supply to tissue oxygen demand. One source of hypoxic dilation via nitric oxide (NO) signaling is nitrite reduction by erythrocytic hemoglobin (α2β2). However, the alpha subunit of hemoglobin is also expressed in resistance artery endothelium and localized to myoendothelial junctions, a subcellular domain that contacts underlying vascular smooth muscle cells. We hypothesized that nitrite reduction mediated by endothelial alpha gl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…A vasodilatory role for alpha globin could be explained by its ability to function not only as a nitric oxide scavenger, but also as a nitric oxide producer via the reduction of nitrite under hypoxic conditions. 27 While the contribution of eNOS activity to vasodilation diminishes with age, the nitrite reductase activity of endothelial alpha globin could potentially persist, thereby explaining the unexpected association of higher HBA copy number with lower diastolic blood pressure in this study of older Black Americans.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A vasodilatory role for alpha globin could be explained by its ability to function not only as a nitric oxide scavenger, but also as a nitric oxide producer via the reduction of nitrite under hypoxic conditions. 27 While the contribution of eNOS activity to vasodilation diminishes with age, the nitrite reductase activity of endothelial alpha globin could potentially persist, thereby explaining the unexpected association of higher HBA copy number with lower diastolic blood pressure in this study of older Black Americans.…”
Section: Discussionmentioning
confidence: 80%
“…This observation implies that increased expression of alpha globin is associated with lower blood pressure, rather than higher blood pressure as hypothesized. Keller et al recently demonstrated that endothelial alpha globin can produce nitric oxide from the chemical reduction of nitrite under hypoxic conditions [30]. Thus, endothelial alpha globin may function not only as a nitric oxide scavenger, but also as a nitric oxide producer.…”
Section: Discussionmentioning
confidence: 99%
“…This observation implies that increased expression of alpha globin is associated with lower blood pressure, rather than higher blood pressure as hypothesized. Keller et al recently demonstrated that endothelial alpha globin can produce nitric oxide from the chemical reduction of nitrite under hypoxic conditions [ 29 ]. Thus, endothelial alpha globin may function not only as a nitric oxide scavenger, but also as a nitric oxide producer.…”
Section: Discussionmentioning
confidence: 99%